Development of an Oriental Medicine Discrimination Method through Analysis of Steroidal Saponins in Dioscorea nipponica Makino and Their Anti-Osteosarcoma Effects - Joo Tae Hwang (Molecules, 2019)
To prevent confusing Dioscorea nipponica (DN), an Oriental medicine, with Dioscorea quinquelobata (DQ) and Dioscorea septemloba (DS), a simple and accurate quantitative analysis method using HPLC combined with ultraviolet (UV) detection was developed and verified with UPLC-QTOF/MS through identification of five saponin glycosides: protodioscin (1), protogracillin (2), pseudoprotodioscin (3), dioscin (4), and gracillin (5). The newly developed analysis method showed sufficient reproducibility (<1.91%) and accuracy (92.1%−102.6%) and was able to identify DN based on the presence of compound 3 (13.821 ± 0.037 mg/mL) and the absence of 5. Compound 1, which is present in DN at a relatively high level (159.983 ± 0.064 mg/mL), was also an important marker for identification. Among the three species, DN showed the strongest activation of apoptotic signaling in osteosarcoma cells, while the four compounds detected in DN showed IC50 values of 6.43 (1), 10.61 (2), 10.48 (3), and 6.90 (4). In conclusion, the strong inhibitory effect of DN against osteosarcoma was confirmed to be associated with 1 and 4, which is also related to the quantitative results. Therefore, the results of this study might provide important information for quality control related to Oriental medicine.